Hydrogen storage for variable renewable electricity integration: Techno-economic analysis of a Lined Rock Cavern system - Ripepi, Giuseppe (My University, 2018)
The following study has been developed in cooperation with Chalmers University of Technology, during an internship in the Energy Division of the Hearth, Space and Environment Department of the same university. The work has been reviewed and discussed within the division and has been mainly followed by the Sustainable European Energy Systems group members Filip Johnsson (co-rapporteur) and Viktor Johansson (PhD student). Finally the thesis was informally defended within the Energy Division. In a future with increasing focus on emissions reduction and industry decarbonization, large-scale energy storage systems will be at the top of the research and development process. There will be the need to smooth electricity production profiles due to an increased renewable energy sources (RES) penetration, which will not probably be managed with the already existing flexibility measures. While some of the storage technologies are already well known and in operation, most of them are only at their early stage of development or even at the research stage. Among the technologies under development it is possible to locate hydrogen storage in all its forms; in particular underground hydrogen storage is seen as a promising technology that can exploit already known gas storage technology. With a particular attention to lined underground rock cavern (LRC) for hydrogen storage, this study aims to understand the hydrogen storage potential in the development of the future energy systems, through a technoeconomic analysis of a system of LRC. While this technology poses a challenge in terms of lining an underground cavern and operate it (the only similar application in operation is a natural gas storage plant based on a LRC system in Skallen, Sweden), on the other hand the excavation process and hydrogen handling are well known procedures, as well as there are several operative hydrogen storage salt caverns worldwide, which can provide specific expertise for the cavern operation. The construction of a LRC system for hydrogen storage would be a challenge in terms of putting together diverse expertise but, as shown by the Skallen facility and the ANGAS project developed by the Japan Gas Association (JPA), this is already possible. The actual definition of large-scale energy storage systems is based on the maximum, already deployed systems capacities: they can reach the range of 1􀀀2GWh, coupled with a power rating of up to 200MW(see figure 1.1) and the only available technologies able to provide those characteristics are compressed air energy storage 2 (CAES) and pumped hydroelectric storage (PHS). However gas storage (as natural gas or hydrogen) can provide much higher storage capacities thanks to its intrinsic high energy density. Here the possibility of store large quantities of hydrogen which can provide, with its energy density of ' 500kWh=m3(based on a pressure of 200bar and a temperature of 20°C), very large storage capacities. With a suitable storage facility it is then possible to store several hundreds of GWh of hydrogen chemical energy, which can be later reconverted into electricity or consumed as raw material to feed industrial, mobility or power to gas (P2G) applications. There are diverse challenges hydrogen must overcome: in order to use it to smooth power profiles, it must be economically sustainable and technically feasible to produce hydrogen from water electrolysis, exploiting RES variable electricity generation, meaning that hydrogen produced through electrolysis must be competitive with traditional hydrogen production technologies; compressed hydrogen in the form of above-ground tanks can be extremely expensive at the moment, so that underground hydrogen storage, possibly in the form of LRC, must be further studied and tested; finally it is important to understand what will be the driver of the hydrogen economy of the future and how and how much it will be interconnected with the power grid.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering